2006
DOI: 10.1002/macp.200600424
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Polyaniline Nanostructures under Ultrasonic Irradiation: From Nanotubes to Nanofibers

Abstract: Summary: An ultrasonic irradiation assisted polymerization method has been used to prepare PANI nanotubes and nanofibers by using different doping concentrations of mineral or organic acids. It has been found that PANI nanotubes can be produced when the concentration of the dopant acid is low. However, PANI nanofibers can also be produced when the concentration of the dopant acid is high. For nanotubes synthesized at a low concentration of the dopant acid, the outer average diameter can be changed from about 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 53 publications
2
44
0
Order By: Relevance
“…When the acidity increases, one-dimensional growth of PANI is promoted, resulting in better contact of the active materials with the electrolyte and in subsequently higher electroactivities. Heterogeneous growth of PANI on initially-formed nanofibrous polymer (secondary growth) was reported to be inhibited in chemical oxidative polymerization of aniline at high levels of acid doping [26]. The triggering of anisotropic growth of low-dimensional PANI at higher acidity in our study should be similarly related to the stronger electrostatic interactions between the polymer chains due to the larger number of positive charges, which originate from the higher degree of protonation [27].…”
Section: Influence Of Acidity On Aniline Polymerizationmentioning
confidence: 82%
“…When the acidity increases, one-dimensional growth of PANI is promoted, resulting in better contact of the active materials with the electrolyte and in subsequently higher electroactivities. Heterogeneous growth of PANI on initially-formed nanofibrous polymer (secondary growth) was reported to be inhibited in chemical oxidative polymerization of aniline at high levels of acid doping [26]. The triggering of anisotropic growth of low-dimensional PANI at higher acidity in our study should be similarly related to the stronger electrostatic interactions between the polymer chains due to the larger number of positive charges, which originate from the higher degree of protonation [27].…”
Section: Influence Of Acidity On Aniline Polymerizationmentioning
confidence: 82%
“…Great efforts have been devoted to avoid this secondary growth including aqueous/organic interfacial polymerization, rapidly-mixed reaction, ultrasonic irradiation, dilute polymerization, etc. to get PANI in fibrous structures [8][9][10][11]. Kaner and coworker demonstrated that the polymerization rate can be controlled through sequent feeding of oxidant solution into aniline solution and nanofibrous PANI was obtained with controlling the oxidant added into aniline solution in small amount [8].…”
Section: Capacitive Properties Of Pani/mno Xmentioning
confidence: 97%
“…Great efforts have been made to suppress this overgrowth by reducing the formation of nucleation sites on surfaces of PANI nanofibers produced in the early stage of polymerization through aqueous/organic interfacial polymerization, rapidly-mixed reaction, ultrasonic irradiation, dilute polymerization, etc. [8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…Great efforts have been devoted to avoid this secondary growth including aqueous/organic interfacial polymerization, rapidly mixed reactions, etc. to get PANI in fibrous structures [26,28]. Kan's group discussed the effect of methanol on electrochemical formation of PANI nano-fibers.…”
Section: Chemical Anchoring Of Silica Nanoparticles Onto Pani Chainsmentioning
confidence: 99%